Effects of combined aerobic and anaerobic training on cardiorespiratory endurance - Sabaananth, S. (University of malaya kuala lumpur, malaysia, 2015)
Introduction: Sports training aim at achieving higher performance in sports competition. In order to achieve higher performance in sports, training should be based on planned and systematic manner. Purpose: The purpose of the study was to find out the effects of combined aerobic and anaerobic training on cardiorespiratory endurance. Methods: To achieve the purpose of the study, seventy five (N=75) male students were selected from University of Jaffna Sri Lanka. The age of the subjects, ranged from 20 to 25 years and randomly divided into five equal groups and each group contain fifteen (n=15) subjects. Group I underwent High intensity of Aerobic (70%) with Low intensity of Anaerobic (30%) training (HALAN), Group II underwent Optimum intensity of Aerobic (60%) with Light intensity of Anaerobic (40%) training (OALTAN), Group III underwent Medium intensity of Aerobic (50%) with Medium intensity of Anaerobic (50%) training (MAMAN), and Group IV underwent Light intensity of Aerobic (40%) with Optimum intensity of Anaerobic (60%) training (LTAOAN) . Group V acted as control. Cardio Respiratory Endurance assessed by using cooper’s 12 minutes run/walk test and all the subjects were tested prior to and after the experimentation. Dependent ‘t’ was used to find out the difference between pre and post test for selected variables and the magnitude of improvement between pre and post data of experimental group was assessed by using percentage calculation on selected criterion variables. Results: The results of the study on Cardio Respiratory Endurance indicate that there was a remarkable improvement observed among experimental groups (HALAN, OALTAN, MAMAN, LTAOAN) and control groups. Conclusion: Hence it may be concluded that OALTAN will be the best method of training to improve Cardio Respiratory Endurance. However HALAN and MAMAN also be adopted to improve Cardio Respiratory Endurance.
Keywords: Aerobic; Anaerobic; Cardiorespiratory endurance.